If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 7 = 6x + 6 Reorder the terms: 7 + 7x = 6x + 6 Reorder the terms: 7 + 7x = 6 + 6x Solving 7 + 7x = 6 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 7 + 7x + -6x = 6 + 6x + -6x Combine like terms: 7x + -6x = 1x 7 + 1x = 6 + 6x + -6x Combine like terms: 6x + -6x = 0 7 + 1x = 6 + 0 7 + 1x = 6 Add '-7' to each side of the equation. 7 + -7 + 1x = 6 + -7 Combine like terms: 7 + -7 = 0 0 + 1x = 6 + -7 1x = 6 + -7 Combine like terms: 6 + -7 = -1 1x = -1 Divide each side by '1'. x = -1 Simplifying x = -1
| -16(x+1)=608 | | -3(2+n)=9 | | 41=8m-15 | | -265-(190)= | | (-4)+5/3 | | 18+3n=3+7+5n | | (x^3-16^2+64)/(x^3-8x^2) | | 9p-18=27 | | 2(x-3)=3(x+2)-3 | | 10(-11-4p)-2p=(-1-3p) | | (5x^3-9x^2+5)-(5-9x^2+5x^3)= | | -5(x-1)+x=6x-5 | | 7p+4=7-2p | | 7x+3(6x+3)=184 | | f(x)=x^2+6x-10 | | 2(675+80n)=2310 | | p/9-5=7 | | x/4-2=5/6+x-4/3 | | (10w-1)(10w+1)=20w | | 6y+2=3y-3 | | 14c-d-7= | | 2/x=-4 | | 3k+15=66 | | ((3x-1)/2)-((5x+4)/3)-((x+2)/8)=((2x-3)/5)-1/10 | | 36-y=-36 | | 7a+3n+3a= | | 4d+12=42 | | x+2+7=40 | | 42-(3c+4)=2(c+4)+c | | 2x+3(2x+15)=125 | | 10(-11-4p)-2p=2(-1-3p) | | 8x-5=1+6x |